Assessing Human Role in Lateral Erosion and Lateral Extension of Gamasiab River in Bistoon Plain - Mahmoud Alaee Taleghani; Farshad Haseli; Majid Ahmadi Molaverdi (جغرافیا و پایداری محیط)
In this study, the role of human has been assessed on lateral erosion and lateral extension of Gamasiyab meanders in Bistoon plain. Human activities on Ghamasiab lateral erosion includes using river material and pumping of water for irrigation. In the recent years, a lot of pumps have been set up on the side of Gamasiab for irrigation. Consequently, when the weakest water reaches to the channel bank in come back, it causes the banks of Gamasiyab canal wearing out and retreat in several ways. This matter has caused the banks of Gamasiyab in few meander strongly wearing out and retreat 30 meters. However, to reach to this aim, the geometrical parameters of 15 meanders that human played an important role in erosion them have been compared with another 19 meanders in a period of 24 years. For this purpose, the satellite images of 1986 and 2010 have been used. First the satellite images were completed from numerically in G I S then circles fixed with meanders and finally the geometric parameters including; wavelength, valley length, central angel, arc radius and the curvature coefficient were measured. Results indicate that the average wavelength of 15 meanders that human interferences on it about 19 meters, the average central angel about 5 degrees, the average arc radius about 26 meters more than another 19 meanders have increased and the valley length decreases about 26 meters less than another meanders. On the basis of this, the curvature coefficient of 15 meanders with human interference increases about 0.13 more than another 19 meanders. In fact, the curvature coefficient of 15 meanders with human interference, have increased from 1.51 in 1986 to 1.7 in 2010, whereas the curvature coefficient of another 19 meanders have increased from 1.22 in 1986 to 1.28 in 2010.